The differences between family firms and non-family firms: Evidence in Indonesia - Farida Titik Kristanti; Riko Hendrawan; Salehudin Eka Saputra Alrasidi (University of Merdeka Malang, 2019)
A family firm is a firm controlled by members of a family through their ownership in the management. This study aimed to observe the presence of differences in gender diversity, cash holding, and financial performance on Family Firms (FFs) and Non-Family Firms (NFFs). The purposive sampling conducted in this study produced 67 samples of companies listed on the Compass 100 Index. They mostly belong to the FF criteria. They also have gender diversity, non-conservative capital structure, medium-size, and low cash holding. The results of difference tests proved the presence of significant differences between the FFs and the NFFs on the variables of firm size, leverage, and gender diversity. Although ROE did not show significant differences, the FFs had higher ROE than the NFFs. Furthermore, the practical implication of this study is the need to consider the presence of women on the board and their share in the firms’ decision making. JEL Classification: G10, G19, G32DOI: https://doi.org/10.26905/jkdp.v23i2.2687